United Nations and Collective Agreements on Global Security: Issues and Perspectives - Kanu, Donald; Oseni, Tunde (Journal of Contemporary International Relations and Diplomacy, 2022)
Owing to the growing threats of pandemics like the Corona Virus (COVID-19) among other emerging infectious diseases, terrorism, genocide, human trafficking, and the proliferation of small arms and light weapons among others, the study assessed the United Nations (UN) on the collective agreement in maintaining global peace and stability. In achieving these, the study adopted the descriptive research design and derived relevant data through the use of semi-structured interviews with respondents randomly chosen from the five permanent member states of the UN Security Council (UNSC). The system theory was employed to provide a clear understanding of the subject matter and the need for institution and collectiveness in the management and sustainability of world peace. However, findings revealed that a restructured UNSC is necessary to give room for a more responsive and all-inclusive organization. This brings to the fore the importance of collective agreements in a multilateral world to collectively and efficiently tackle the contemporary threats to world peace and stability.